2017
DOI: 10.1038/srep46019
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic mutations in the gene encoding eEF1A2 cause seizures and sudden death in F0 mice

Abstract: De novo heterozygous missense mutations in the gene encoding translation elongation factor eEF1A2 have recently been found to give rise to neurodevelopmental disorders. Children with mutations in this gene have developmental delay, epilepsy, intellectual disability and often autism; the most frequently occurring mutation is G70S. It has been known for many years that complete loss of eEF1A2 in mice causes motor neuron degeneration and early death; on the other hand heterozygous null mice are apparently normal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…Although the effects on gene expression of 6-OHDA and eft-3/4 gene silencing were different, the anti-apoptotic genes were strongly suppressed when both treatments were combined. The previous findings showed that the downregulation of eEF1A1 causes the neurons to be more vulnerable to the external insults (Vera et al, 2014;Davies et al, 2017), and our results further showed that the downregulation of eEF1A2 also increases sensitivity to external insults. Our data encourage the fact that the downregulation of eft-3/4 attenuates the neurons to be more vulnerable to neurotoxin by suppression of the antiapoptotic genes as well as the promotion of some apoptotic gene expressions.…”
Section: Discussionsupporting
confidence: 85%
“…Although the effects on gene expression of 6-OHDA and eft-3/4 gene silencing were different, the anti-apoptotic genes were strongly suppressed when both treatments were combined. The previous findings showed that the downregulation of eEF1A1 causes the neurons to be more vulnerable to the external insults (Vera et al, 2014;Davies et al, 2017), and our results further showed that the downregulation of eEF1A2 also increases sensitivity to external insults. Our data encourage the fact that the downregulation of eft-3/4 attenuates the neurons to be more vulnerable to neurotoxin by suppression of the antiapoptotic genes as well as the promotion of some apoptotic gene expressions.…”
Section: Discussionsupporting
confidence: 85%
“…These observations suggest that heterozygous complete loss‐of‐function variants may be lethal in humans. In null mouse models, complete loss of eEF1A2 is lethal by 28 days and mice exhibit a muscle wasting phenotype with or without seizures, while heterozygous mice display no overt phenotype (Chambers et al, 1998; Davies et al, 2017). Moreover, in small studies, mice carrying a p.Gly70Ser missense variant either in the homozygous state or in combination with a CRISPR‐generated indel on the other allele, were phenotypically indistinguishable from complete null mice (Davies et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, the expression is limited to the brain (Figure S2). eEF1A2 knockout mice display early‐onset neurodegeneration and muscle wasting (Chambers, Peters, & Abbott, 1998), as well as spontaneous seizures and sudden death in another null mouse model (Davies et al, 2017). In contrast, heterozygous mice are normal (Chambers et al, 1998; Davies et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Concentration of protein lysates was determined using either the Pierce BCA protein assay kit (Pierce) or the DC Protein Assay (Bio-Rad) following the manufacturers' instructions. Western blotting was carried out using near-infrared detection method by LI-COR as previously described in [36]. Protein detection was also performed using the chemiluminescence method.…”
Section: Protein Analysismentioning
confidence: 99%